Exploring the acceptability of three time‐matched exercise interventions for increasing fitness in women living with obesity: A mixed‐methods evaluation of the EXOFFIT study - Mary E. Davis; Caitriona Cunningham; Catherine Blake; Gráinne O'Donoghue (Wiley, 2024)
Abstract Background The EXOFFIT study compared the effectiveness of three time‐matched exercise interventions in women with obesity for improving cardiorespiratory fitness. To best inform future research, evaluation of the interventions' acceptability is needed. Previous research has been inconsistent with methods and reporting of acceptability. Thus, the theoretical framework of acceptability (TFA) can be utilized to ensure that all aspects of acceptability are evaluated. No study to date in women with obesity has utilized the TFA in conjunction with quantitative data (i.e., frequencies of themes) to highlight the aspects of interventions that may be most important for participants. Objective This study aimed to examine the acceptability of the EXOFFIT program and gain insight into the participants' experience of participation, their perspective on the acceptability of trial procedures and interventions and gather their feedback on program changes. Methods A mixed‐methods approach was employed. Thirty‐eight participants who completed the exercise interventions were interviewed and completed a self‐reported exit questionnaire. Interviews were transcribed verbatim and analyzed in three phases: emergent themes were agreed upon, then mapped to the TFA constructs and the frequencies of each construct and theme were presented as counts. Data collected from the exit questionnaire were collated and reported using descriptive statistics. Results All seven TFA constructs were identified in the analysis. The EXOFFIT program was found to have a high level of acceptability, with affective attitude, perceived effectiveness and self‐efficacy being the most reported constructs. The burden and opportunity costs associated with the program were mainly related to family commitments and support needed to participate. Any negative impact of participation was noted to be outweighed by the perceived benefits. Conclusions The results of this study will inform the development of future programs with women with obesity and support the consideration of the TFA constructs from the outset of study design. Clinical Trial Registration Number: ISRCTN13517067